PENGARUH VARIASI AGREGAT KASAR PENYUSUN BETON TERHADAP KERAPATAN BETON DENGAN MENGGUNAKAN TRANSMISSION TIME PADA ALAT UPV (ULTRASONIC PULSE VELOCITY) - Fatma Dora Indriani; Christin Remayanti Nainggolan; Ming Narto Wijaya (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
To find out the quality of concrete, we need to test the concrete. Which is non destructive test or testing without damaging the test object, namely with an UPV (Ultrasonic Pulse Velocity). In this study using 4 variations of coarse aggregate composition (mix design), namely porous variation, RCA (Recycled Coarse Aggregate) variation, pumice variation and fiber variation. The UPV test results in this study show that the relationship of compressive strength with amplitude (A1) or transmission time (t0) is concluded that the low homogeneity value causes higher energy loss so the amplitude value becomes lower and the value transmission time depends on the density of the concrete. In the value of compressive strength that affects homogeneity, it does not mean the higher the uniform material (homogeneity), the higher the compressive strength value. Keywords: Amplitude, Concrete, Compressive Strength, Ultrasonic Pulse Velocity, Transmission Time